The Effect of the Realistic Mathematics Education (RME) Approach on Fifth-Grade Students’ Mathematical Conceptual Understanding in a Public Elementary School in Bandung - Triwahyuni, Ida; Sopandi, Wahyu; Arisetyawan, Andika; Wulandari, Hesti (International Conference on Elementary Education, 2025)
Understanding mathematical concepts is an important skill in developing numeracy literacy in elementary school students. However, initial observations at SDN Bandung 1 in Serang District show that some fifth-grade students still have difficulty understanding basic mathematical concepts, especially in the subject of fraction calculations. This occurs because learning is still teacher-centered and does not sufficiently relate mathematical concepts to real-life contexts. This study aims to determine the effect of the Realistic Mathematics Education (RME) approach on students' understanding of mathematical concepts. The method used is quantitative with a quasi-experimental design of the nonequivalent control group type. The research sample consisted of 41 students, namely 21 students in the experimental class and 20 students in the control class. The results of the analysis using the t-test showed a t-value of 3.52 > t-table = 2.02 at a significance level of 0.05. The average posttest score of the experimental class was 82.90, which was higher than that of the control class, which was 73.45. These results indicate that the RME approach has a significant effect on improving students' mathematical concept understanding and helps them understand abstract concepts through more contextual and meaningful situations.